(untitled) (European Journal of Pure and Applied Mathematics, 2023)
This paper deals with the concepts of upper and lower weakly α(Λ, sp)-continuous multifunctions. Moreover, several characterizations of upper and lower weakly α(Λ, sp)-continuous multifunctions are established.